CONTRIBUTIONS OF “KNOWLEDGE” IN WORLD ECONOMY - CIOBAN, Gabriela-Liliana (Ecoforum Journal, 2016)
The effect of knowledge globally is reflected in the growth / development of national economies and improvement of living standards of the population. Arguments underlying this statement are reflected in the values ​​held by certain indicators (Knowledge Economy Index, Gross Domestic Product, Index of Innovation, Knowledge Intensive Services etc.) and their effects on national economies. Factors contributing to the development of these indicators are the "key" to success in each economy and also part of their basic foundation. The explanation so far obliges us to analyze current global economic situation and its prospects. As a first step we will try to answer the question "What is the generator factor of growth / prosperity in different countries?" and to identify its evolution over time. A second stage of the study will represent an analysis in the architecture centers of power due to the competitive advantage held by certain countries / companies in creating wealth. The study is based upon emergence and strengthening of competitiveness in the businesses and the national economy. Knowledge-intensive services’ presence in the world's economies is a vital source of economic growth.